Kajian Bibliometrik Untuk Menemukan Kebaruan dalam Penelitian Mengenai Berpikir Kritis - Alam, Sri Rahayu; Suparman, Suparman; Samsinar, Samsinar; Siswanto, Deny Hadi; Genius, Dinda; Maretha, Anggun (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
Research on critical thinking has been done a lot. There are approximately 1,983 studies on critical thinking over the last 10 years. This study aims to classify 100 articles about critical thinking to find research novelty based on 6 categories. The first is based on the product development model, the second is based on learning tools, the third is based on the learning model, the fourth is based on education level, the fifth is based on class, and the sixth is based on subjects. This type of research is study literature. The results showed: 1) Novelty in the product development model category using the PDD model; 2) Novelty in the category of learning devices using teaching materials; 3) Novelty in the learning model category using the BSMT, ER, Culture-Based 7E Learning Cycle, Jigsaw, Remap GI & Remap J, RECORSE, 5E-STEAM, RME, PJBL, Active and Interactive Learning models; 4) Novelty in the category of education level is carried out in PAUD; 5) Novelty in the class category is carried out in grade 9; and 6) Novelty in the subject category using PAI, accounting, ICT, and social subjects.